QUO VADIS AKSI 22 LASKAR PEMBELA ISLAM MENOLAK TEMPAT PROSTITUSI DI KABUPATEN PAMEKASAN DALAM BINGKAI SOCIAL MOVEMENT - Abu Muslim (Bahasa Indonesia, 2020)
This paper aims to reveal how the Islamic Defenders Army, under the affiliation of FPI, carried out the 22 January action against the closure of the protest site in Pamekasan. This article originated from the issue of the LPI sweeping action in Langtolang Hamlet, Ponteh Village, Pamekasan which was charged as an illegal protest site in Pamekasan but resulted in violence and clashes. In the following incident, the Islamic Defenders Army group carried out 22 actions regarding the closure of the protest center in Pamekasan at the Regent's office. This marks a social, political, and symbolic event that is quite complex and interesting to discuss. Talking about symbolic events is ambiguous. In this incident, however, the people of Pamekasan knew that what was called the Defense Action 22 was an opportunistic response to protists in Pamekasan that violated local regulations and Islamic law. First, where this action is seen as a representation of Pamekasan Muslims as a Muslim identity, such as the implementation of Shari'ah law. Second, this event has provided the Laskar Pembela Islam (LPI) opportunity to erase the collective memory of the violence they have committed through political currents